Caracterização física, físico-química e química do fruto da aceroleira (Malpighia emarginata DC), variedade Okinawa, durante o seu desenvolvimento. - Maranhão, Christine Maria Carneiro (2010)
Acerola is a tropical fruit of great economic and nutricional potential, mainly, had to its high vitamin text C. The ripeness process is one of the processes most important in the fruit that involves changes in the acid texture, color, sugars and, what it is an important factor in the quality. Being thus, the objective of this work was to evaluate the physical changes, physical chemistries and occured chemistries during the cycle of development of acerola, aiming at to get subsidies in the determination of the maturation indices. The following determination had been carried through: equatorial and polar, weight, volume, total and reducing degree of color, humidity, protein, leached ashes, sugars, pectin, diameter, pH, total soluble solids, titratable acidity, chlorophylls a and b, anthocyanins, flavonols, carotenoids. With regard to the inference of the data, adjustment of models of regression with application of Statistical Test F. When comparing was carried through the text of carotenoids, flavonols, clorofila and anthocyanins proves a significantly bigger text of these constituent in the rind. The stage of development (opening of the flower until the ripeness) of acerola understood a period of 25 days in the winter corroborating with literature. The results of the analyses of total and reducing, solid sugars soluble totals, the decrease of chlorophylls, appearance of the anthocyanins and solubilização of the acid pectic allow to infer that the beginning of the maturation occurred 19º day after antese. Acerola in the mature stage is distinguished for presenting significant texts of these bioativos composites as carotenoids, anthocyanins, flavonols and acid ascobic that make of this fruit a promising antirust composite source whose culture would have to be stimulated.